Use of local isolate of Monascus purpureus for reducing blood cholesterol in Sprague Dawley rat - ERNAWATI KASIM; YETY KURNIAWATI; NOVIK NURHIDAYAT (Society for Indonesian Biodiversity, 2006)
Research using local isolate of M. purpureus to reduce the blood cholesterol total on the white rats of Sprague Dawley strain had been done. The research proposed was to obtain the best doses of fermented rice contain lovastatin to reduce the blood cholesterol content of the white rats Sprague Dawley strain. The research used 42 male rats which was devided into 6 treatments based on the food and fermented rice doses. Each rat was 2 months and 250 gram in weight. The cholesterol food and the standard food given everyday for 20 gram/day/rat. The blood rats was measured the content of cholesterol every seven days for 21 days. The result showed that the lovastatin of the fermented rice could reduce 20,78% the blood cholesterol total of the white rats Sprague Dawley strain. Â© 2006 Jurusan Biologi FMIPA UNS SurakartaKey words: Monascus purpureus , kolesterol, tikus putih galur Sprague Dawley